Factors interfering screening for gynecological cancers in peruvian women: Factores que interfieren los cribados para cánceres ginecológicos en mujeres peruanas - Silva-Lopez, Carmen M. (2022)
Objective: To identify the factors associated with the interference of gynecological cancer screening in women aged 25-69 years, according to the Demographic and Family Health Survey (ENDES) for the years 2019 and 2020. Materials and methods:  Quantitative, observational, analytical cross- sectional study. It was a secondary database analysis obtained by ENDE for the years 2019 and 2020. Generalized linear Poisson family crude and adjusted models were used to estimate the association. The measure of association. The measure of association used was the adjusted prevalence ratio (Rpa) with 95% confidence interval (95% CI). Results: We worked with a total of 18,113 women aged 25-69 who were interviewed at the ENDES 2019-2020. In the descriptive analysis, it is observed that 19.3% did not take a PAP smear (PAP) and 53.6% did not perform “screening for breast cancer”. Women with a primary education level have 19% and 58% more opportunities to present interference for taking PAP and screening for breast cancer respectively (RPa: 1,19, 95% CI 1.08-1,31 and RPa:1.58, 95% CI 1:51 – 1:64). Living in the jungle increases 56%and 20%more chance of presenting interference for taking PAP and screening for breast cancer respectively (RPa: 1.46, 95% CI 1.42-1.71 and RPa: 1.20, 95% CI: 1.15- 1.25). The level of knowledge increases the interference for taking PAP and screening for breast cancer by 43% and 3% respectively (RPa: 1.43, 95% CI: 1.34- 1.54 and RPa: 1.03, 95% CI:1.00 -1.06) Conclusions: Sociodemographic, sociocultural and economic factors have a marked influence on the performance of gynecological cancers such as cervical cancer and breast cancer, so it is necessary to implement strategies to promote the prevention of these pathologies.